Light verb constructions as complex verbs. Features, typology and function - Pompei, Anna; Mereu, Lunella; Piunno, Valentina (Mouton de Gruyter, 2023)
The notion of light verb constructions has been traditionally related to the ‘insignificance’ of the verb, which is described as a grammatical item only codifying TAM system and φ-features, whereas the whole predicative content is thought to be conveyed by the noun. This book deals with the light verb constructions as instances of complex verbs, intended as multi-predicational but monoclausal structures. This allows to deepen the actual verb lightness, the effective noun predicativity, as well as their effect on the cohesion of the construction. The papers in this volume reflect on the concrete contribution of noun and verb to the event and argument structure, and on the relevance of semantically different noun classes for the verb selection. From different theoretical approaches, data of a great variety of languages are investigated, such as Indo-European languages – both modern (Germanic, Slavic, Romance and Iranian languages) and ancient (Latin and Ancient Greek) – but also Mandarin Chinese, and different polysynthetic languages (e.g. Ket, Nivkh, Murrinh-Patha, Kiowa, Bininj Gun-wok, Ainu). The range of topics, languages and perspectives presented in this book make it of great interest to both theoretical and applied linguists.